(untitled) (REMUNOM, 2025)
Sheep and goat farming is an important economic activity and a source of food security in Brazil, especially in small- and medium-scale production systems. However, the productivity of sheep and goats is compromised by gastrointestinal parasitoses, mainly helminth infections caused by nematodes, which negatively affect animal health and productive performance. Anthelmintic resistance, resulting from the frequent and improper use of dewormers, has spread across herds in several regions, representing a serious sanitary and economic challenge. This study reviews the main factors associated with resistance, such as genetic mechanisms of parasites, inadequate management practices, and indiscriminate drug use. Integrated control strategies, including selective treatment, rotation of active compounds, and monitoring through parasitological and molecular methods, are presented as effective solutions to slow resistance development and promote production sustainability. Thus, the implementation of responsible management practices is essential to ensure animal health and the economic viability of sheep and goat farming in Brazil.